THE MECHANICAL SYSTEM DESIGN IN TACTICAL GROUND VEHICLE (TGV) FOR AKSUS TEAM PASKHAS COMMAND BATTALION - Aris Tri Ika Rakhmadi; Endro Endro; Supriyadi Supriyadi (JOURNAL ASRO, 2022)
One of the tasks of the PDR Team (Indoor Combat) is to become the Matan Team (Security and Rescue) which has special duties in daily operations, including the task of security operations for VIPs/VVIPs who are in ring one security. From this task, the PDR Team needed an infiltration tool that was used closer to the target to get the latest visual image information and was able to carry weapons that could paralyze the enemy if needed. Therefore we need a design method to make a tool using a remote control. The mechanism of this tool frame is designed using hollow stainless steel pipe with a size of 1.5 cm x 1.5 cm and a thickness of 1 mm. The tool body uses an iron plate with a thickness of 1 mm for the placement of the driving components, namely the DC electric motor, pillow block holder, and other supporting components. The operation of the tool uses a chain and sprocket transmission system with a 12 V battery energy source using 2 DC motors with a power specification of 110.74 watts, 2000 rpm, obtained a speed of 1.84 m/s. From the DC motor to the axle (16 mm diameter) connected by a chain that is used to drive the wheels, this tool is able to withstand and support the entire load on the TGV with a total load of 50.6 kg. From the testing of the tool that has been carried out for approximately 6 months, it has succeeded in moving as expected, namely being able to shoot at targets using a 9 mm caliber short-barreled weapon effectively in the implementation of exercises and operations of the Matan/PDR Team. This tool is equipped with a camera that is connected to a remote monitor screen, so that the Operations Commander can make faster, more precise and accurate decisions according to field conditions. Keywords : Camera, Chain and Sprocket, DC Motor, Short Barrel Weapon, Remote.